Acute leptin response after high intensity interval and moderate intensity continuous runs - Rodrigues, A.; De Lucca, L. (European Journal of Human Movement, 2020)
The possible direct role of exercise intensity and duration on leptin concentrations is conflicting. The aim of this study was to evaluate the acute effects of high intensity interval (HIIE) and moderate intensity continuous (MICE) exercise on plasma leptin response. Seven young volunteers underwent three tests: 1) a treadmill graded exercise test to identify running peak velocity (PV); 2) HIIE: 5 × 2 min work bouts at 90% of PV, interspersed by 2 min of passive recovery and; 3) MICE: 30 min at 70 % of PV. Blood samples were drawn for the assays of leptin before and 30 minutes after HIIE and MICE. A 2-way repeated measures ANOVA showed a significant main effect of time [F(1,6) =17,52; p=0,006], no significant effect of condition (type of exercise) (F(1,6) = 0,16; p = 0,68) and no significant interaction (condition × time) (F(1,6)= 0,48, p=0,51). Leptin decreased 30 min after HIIE (t= 2,95, p=0,025) and MICE (t=4,18; p=0,005). There was no difference between the HIIE and MICE conditions immediately after exercise (t=0,90; p=0,40). After HIIE and MICE, leptin decreased in the same magnitude. It appears that both exercise modalities result in physical stress which is sufficient to improve short-term leptin sensibility.